Parenting Styles, Internalization of Values and Self-Esteem: A Cross-Cultural Study in Spain, Portugal and Brazil - Martínez, Isabel (2022)
The present study analyzes the impact of parenting styles on adolescents’ self-esteem and internalization of social values in three countries, Spain, Portugal and Brazil. The sample of the study was comprised of 2091 adolescents from Spain (n = 793), Portugal (n = 675), and Brazil (n = 623) from 12–18 years old (52.1% females). The four types of parenting styles, authoritative, indulgent, authoritarian and neglectful, were measured through the warmth and strictness dimensions of the Scale of Parental Socialization ESPA29. The two criteria variables were captured with the five dimensions of the AF5, Five-Factor Self-Concept Questionnaire, and with self-transcendence and conservation Schwartz values. Results confirm emergent research in parenting socialization: the use of parental warmth is evidenced as key for adolescent self-esteem and internalization of social values in the three countries analyzed. Indulgent and authoritative parenting (both characterized by parental warmth) are associated with the highest value internalization in the three countries. Furthermore, indulgent parenting (use of warmth) is associated with the highest adolescent self-esteem, overcoming authoritative parenting (use of warmth and strictness). The influence of parenting over adolescent self-esteem and values internalization is maintained independent of the differences in self-esteem and value priorities observed in the cultural context, the sex and age of the participants.